POLITIK HUKUM PENGATURAN PENGADAAN TANAH UNTUK PEMBANGUNAN BAGI KEPENTINGAN UMUM - Hamidah, Upik (Fakultas Hukum Universitas Lampung, 2012)
The reaserch studied about political low of land provision arrangement for public needs building. the research used empiric juridical approach. the result of study indicated thet the political law of land provision arrangement for public needs building had been changed. perpres no. 65 year of 2006 and UU no.2 year of 2012 referred to the land provision by loosing the righets on behafs of land, and it tendend moderately and can honor society righets on behalf of lands.